PENGARUH STEREOTIP GENDER TERHADAP PILIHAN JURUSAN PENDIDIKAN (STUDI EMPIRIS PASA SISWA SMK NEGERI DI KOTA SORONG) - Madina, La Ode; Palilu, Aram (LPPM Politeknik Saint Paul Sorong, 2024)
This research was conducted to examine the influence of gender stereotypes on the choice of education major (empirical study of state vocational school students in Sorong City). This research used a sample of 98 State Vocational School students in Sorong City. The data collection techniques used were observation, distributing questionnaires and documentation. The data analysis technique is quantitative data analysis using simple linear regression. The research results shown by the t-calculated value are 4.903 with a significant value of 0.000. If the significant value is compared to 0.000 < 0.05, the decision in this research is to accept the Ha hypothesis and reject H0 and it can be interpreted that gender stereotypes influence the choice of education major at State Vocational Schools in Sorong City. Apart from that, based on the determinant coefficient test, the R square value is 0.200, so the contribution of the Gender Stereotype variable (X) to the educational major choice variable (Y) is 20% and the remaining 80% (100% - 20%) is determined by other factors that influence the choice of major. education at state vocational schools.